Settling analysis of MOS regulated current mirrors applied to micropower D/A converters - De Lima, J. A. (Kluwer Academic Publ, 2000)
This paper provides an insight to the trade-off between settling time and power consumption in regulated current mirrors as building parts in micropower current-switching D/A converters. The regulation-loop frequency characteristic is obtained and difficulties to impose a dominant-pole condition to the resulting 2nd-order system are evaluated. Raising pole frequencies in micropower circuits, while meeting consumption requirements, is basically limited by parasitic capacitances. For such cases, an alternative is to impose a twin-pole condition in which design constraints are somewhat relieved and settling slightly improved. Relationships between pole frequencies, transistor geometry and bias are established and design guidelines for regulated current mirrors founded. By placing loop-transistors in either weak or strong inversion, small (W/L) ratios are allowed and stray capacitances reduced. Simulated waveforms suggest a good agreement with theory. The proposed approach applied to the design of a micropower current-mode D/A converter improves both simulated and experimental settling performance.
Keywords: micropower design; MOS regulated-cascode circuits; D/A converter; current mirrors